Drug Use Stigma and Reprisal: Barriers to Prison Needle Exchange in Canada - De Shalit, Ann (The prison journal, 2024)
After years of advocacy by a range of civil society groups, supported by scholarly and empirical research, Canada's federal prison service implemented a needle exchange program at select carceral institutions in 2018. Since the program rollout, however, uptake has remained minimal. To understand why, we conducted the first independent and national study of the program, interviewing 30 people who were incarcerated at one of the prisons with a needle exchange. Our findings show that drug use stigma and anticipated or actual reprisal from correctional officers, particularly related to breaches of confidentiality for program participants, markedly impede access and utilization.